Respuesta :

Given:

The expression is:

[tex]2\log_5(5x^3)+\dfrac{1}{3}\log_5(x^2+6)[/tex]

To find:

The single logarithm expression for the given expression.

Solution:

We have,

[tex]2\log_5(5x^3)+\dfrac{1}{3}\log_5(x^2+6)[/tex]

Using properties of the logarithm, we get

[tex]=\log_5(5x^3)^2+\log_5(x^2+6)^{\frac{1}{3}}[/tex]           [tex][\because \log x^n=n\log x][/tex]

[tex]=\log_5(25x^6)+\log_5\sqrt[3]{x^2+6}[/tex]

[tex]=\log_5(25x^6)\sqrt[3]{x^2+6}[/tex]          [tex][\because \log a+\log b=\log (ab)][/tex]

Therefore, the correct option is B.

ACCESS MORE